Javanese Religious Humanism (Critical Study of R.M.P. Sosrokartono) - M. Agus Wahyudi; Syamsul Bakri (Islah: Journal of Islamic Literature and History, 2021)
Humanism is a school in philosophy which states that humans are the center of everything, or referred to as anthropocentric. So it gives a negative impression of humanism itself. There is a discourse that God is removed or not functioned with the understanding of humanism that upholds the values of human beings. Javanese society is famous for its friendly, humanist and religious people in religion. One of the figures who came from Java was R.M.P. Sosrokartono, he has ideas and thoughts that indirectly contain humanistic values that are wrapped in the values of Javanese society. This study uses descriptive qualitative methods, the data in this study there are two forms, primary data and secondary data. The purpose of this study is to reveal the values of humanism in the thinking of R.M.P. Sosrokartono and how it is relevant to today's life. The result of this research is that there are teachings of R.M.P. Sosrokartono name is ilmu kantong bolong dan ilmu kantong kosong, in which there are humanistic values. In addition, the humanism model of R.M.P. Sosrokartono has a new variant with the humanism that developed in the West.